Bottom-Up and Top-Down Effects of Forest Fragmentation Differ Between Dietary Generalist and Specialist Caterpillars - Anderson, Riley M.; Dallar, Nicole M.; Pirtel, Nikki L.; Connors, Christian J.; Mickley, James; Bagchi, Robert; Singer, Michael S. (Frontiers in Ecology and Evolution, 2019)
Ecological interactions increasingly occur in the context of anthropogenic landscape alteration, such as landscape fragmentation, which engenders numerous changes to abiotic and biotic processes. Theory and empirical evidence suggest that species that are ecologically specialized or positioned at higher trophic levels are most sensitive to the effects of landscape fragmentation, yet the mechanisms underlying this sensitivity remain hypothetical. Here we present an initial test of the hypothesis that landscape fragmentation affects tri-trophic interactions more severely for dietary specialist than for generalist insect herbivores. We specifically tested a bottom-up hypothesis, that fragmentation reduces hostplant food quality to herbivores, with the most pronounced effects for dietary specialists. We also tested a top-down hypothesis, that fragmentation reduces parasitism of caterpillars, with the most pronounced effects on dietary specialists. We studied interactions among trees, caterpillars, and parasitoids in forest fragments (3 – 1013 ha) in Connecticut, U.S.A. in 2017 and 2018. To address the bottom-up hypothesis, we measured the growth performance of multiple dietary specialist and generalist caterpillar species fed leaves from red maple and witch hazel trees sampled from large or small forest patches. We assessed the top-down hypothesis by quantifying mortality from insect parasitoids of many of the same caterpillar species on these tree species sampled from a range of forest patch sizes. Fragmentation did not reduce herbivore growth performance for either dietary specialist or generalist caterpillars even though it accelerated desiccation rates of leaves of both tree species over the growing season. However, dietary specialization increased herbivore sensitivity to yearly variation in food quality, as the growth efficiency of specialist caterpillars varied between 2017 and 2018, while that of generalist caterpillars did not. As predicted, parasitism rates of dietary specialist caterpillars declined as forest fragment size declined, whereas parasitism of generalists was independent of fragment size. Therefore, interactions involving dietary specialist herbivores were most sensitive to top-down environmental variation. Assuming that dietary specialist caterpillars are primarily attacked by host-specific parasitoids, this top-down effect is consistent with the trophic theory of island biogeography, which predicts the sharpest declines of ecologically specialized predators and parasites in small habitat patches.